PERKEMBANGAN DAN PENINGGALAN ISLAM DI MASJID RAYA AL MASHUN - Ika Purnamasari; Ailin Zebua; Azizah Mawaddah; Perdin Hasudungan Panjaitan; Uly Sirait; Yunus May (STKIP Subang, 2026)
The Al-Mashun Grand Mosque is a historical Islamic heritage that has played a significant role in the development of Islam in Medan. Built during the Deli Sultanate, the mosque serves not only as a place of worship but also as a center for religious, educational, and social activities. This study aims to examine the development of the Al-Mashun Grand Mosque over time and identify various Islamic relics that are still preserved to this day. The method used is a qualitative method with a historical approach through literature studies and observation. The results show that the Al-Mashun Grand Mosque has experienced significant development, both in terms of function and its role in society. Furthermore, the mosque also preserves various historical relics such as distinctive architecture that blends Middle Eastern, Indian, and European elements, Islamic calligraphy ornaments, and preserved Malay cultural values.